2015
DOI: 10.1111/hiv.12212
|View full text |Cite
|
Sign up to set email alerts
|

Declines in highly active antiretroviral therapy initiation at CD4 cell counts ≤ 200 cells/μL and the contribution of diagnosis of HIV at CD4 cell counts ≤ 200 cells/μL in British Columbia, Canada

Abstract: Objectives The aim of the study was to examine trends in initiating highly active antiretroviral therapy (HAART) with a CD4 count ≤ 200 cells/µL and the contribution of having a CD4 count ≤ 200 cells/µL at the time of diagnosis to these trends, in British Columbia (BC), Canada. Methods We included in the analysis treatment-naïve BC residents aged ≥ 19 years who initiated HAART from 2003 to 2012. Participants were classified as follows: Group 1: diagnosed and initiated HAART with a CD4 count > 200 cells/µL; G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
3
13
2
Order By: Relevance
“…Consistent with prior results from BC, older age was associated with late and delayed ART initiation (Lourenco et al, 2015;Palmer et al, 2014). Notably, other research has found younger age to be associated with attrition in HIV care over time (Lourenco et al, 2014), suggesting a missed opportunity to retain younger people.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with prior results from BC, older age was associated with late and delayed ART initiation (Lourenco et al, 2015;Palmer et al, 2014). Notably, other research has found younger age to be associated with attrition in HIV care over time (Lourenco et al, 2014), suggesting a missed opportunity to retain younger people.…”
Section: Discussionsupporting
confidence: 84%
“…Based on prior studies in BC, variables we expected to predict late initiation included the history of IDU, HCV seropositivity, and lower income (Joseph et al, 2016;Lourenco et al, 2015;Palmer et al, 2014). Our findings may reflect changing characteristics of new initiators in BC, or may be due to limited sample size and a high percentage of participants with a history of IDU and HCV seropositivity, which left little room to examine variability.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Other priority populations identified in Ontario's HIV/ AIDS strategy include people who use drugs and at-risk women [43], and we observed interesting findings for both. Participants who had ever injected drugs in our analysis were less likely to be diagnosed or present to care late, a finding also observed in other jurisdictions [28,44,45]. People who inject drugs may be a more accessible group to whom testing can be offered via harm reduction services (e.g.…”
Section: Discussionsupporting
confidence: 60%
“…2 The inhibition of virus replication permits restoration of the immune system thereby preventing or delaying the clinical progression of HIV disease. 3,4 HAART has resulted in substantial reductions in HIVassociated morbidity and mortality. 4,5 changing an HIV diagnosis into a manageable chronic infection in Ethiopia even though there is a regional variation in the extent of its benefit.…”
Section: Introduction Backgroundmentioning
confidence: 99%